Does Alcohol Advertising Effect Young People’s Alcohol Consumption? – A Systematic Review. - Clift, Jonathan (2011)
Aim: To explore the claim that alcohol advertising has an effect on young people’s levels of alcohol consumption. Methods: Studies were identified using a systematic search from September 2010 to December 2011. Wiley Interscience, Science Direct, Pubmed, Ovid Online and Google scholar were used to search studies that that were no older than 15years of age, participant age from 10 to 26years old and were of primary research design.